2018
DOI: 10.1111/modl.12514
|View full text |Cite
|
Sign up to set email alerts
|

Educators’ Target Language Varieties for Language Learners: Orientation Toward ‘Native’ and ‘Nonnative’ Norms in a Minority Language Context

Abstract: Target varieties for language learning are contentious in applied linguistics and sociolinguistics. Debates centre on the nature and utility of alternative norms. Approximation to ‘native speaker’ practices is the hallmark of language education. Thus, policy and pedagogy frequently orient toward achieving native‐like production. While many language learning stakeholders are committed to this model, it is also contested. Opponents point to the ideological assumptions about ‘native’ and ‘nonnative’ speech inhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 71 publications
3
22
0
Order By: Relevance
“…The study concluded that positive teacher attitudes and interventions using the minority language is crucial for the inclusion of both minority and majority languages in bilingual education programs. Similar conclusions have reached other studies, for instance, in the Irish case teaching Irish minority language, Ó Murchadha and Flynn [43] state that teachers are key in reinforcing Irish and its varieties in the schooling setting.…”
Section: Teachers' Perceptions When Teaching Minority Languagessupporting
confidence: 87%
“…The study concluded that positive teacher attitudes and interventions using the minority language is crucial for the inclusion of both minority and majority languages in bilingual education programs. Similar conclusions have reached other studies, for instance, in the Irish case teaching Irish minority language, Ó Murchadha and Flynn [43] state that teachers are key in reinforcing Irish and its varieties in the schooling setting.…”
Section: Teachers' Perceptions When Teaching Minority Languagessupporting
confidence: 87%
“…Monolingual bias undergirds the idea that ultimate attainment in language learning is to speak like a monolingual native speaker of the target language (Cook, 1999(Cook, , 2016. It also informs our notion that the highest form of language is a named national standard with clear prescriptive boundaries (García & Wei, 2014;Ó Murchada & Flynn, 2018;Spolsky, 2002), and expertise is best gained by exclusively communicating in and being surrounded by it. Thus, monolingual immersion is imposed in WL programs to create classroom environments believed to be optimal for learning.…”
Section: Introductionmentioning
confidence: 78%
“…12 Issue 1 (2020) 5 second language (L2) users regardless of whether they approximate L1 norms (Cook, 2007). Whereas some research has adopted the practice of referring to 'native speakers' as 'L1 users' (e.g., Dewaele, 2018;Resnik, 2018), the term and concept of the native speaker lives on in the minds and vocabulary of learners (e.g., White, 2016), language programs, and other research (e.g., Barron, 2019;Nguyen, 2019;Ó Murchadha & Flynn, 2018). Because the assumption of cultural consensus and community-specific NS norms is the focus of the current investigation, the term NS is used in this paper, however, not with the intention to validate but rather to interrogate its problematic underpinnings.…”
Section: Cultural Consensus and Native Speaker Communities In Fl Teacmentioning
confidence: 99%